2019
DOI: 10.1186/s13068-019-1454-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of alkaline hydrogen peroxide pretreatment and Tween 80 to enhance enzymatic hydrolysis of sugarcane bagasse

Abstract: Background Due to the intact structure of lignocellulosic biomass, pretreatment was a prerequisite to improve the enzymatic hydrolysis by disrupting the recalcitrant lignocellulose and increasing the accessibility of cellulose to enzyme. In this study, an alkaline hydrogen peroxide (AHP) pretreatment of sugarcane bagasse with various loadings of H 2 O 2 (1.25–6.25 wt%) at temperatures of 60–160 °C was proposed to degrade hemicellulose/lignin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…However, peak disappear at 1,324, 1,514 and 1604 cm − 1 when bagasse subjected to alkali pretreatment was deligni ed more e ciently in comparison with the acid pretreatments and un-treated sugarcane bagasse. Chandel et al, [14] and Zhang et al, [32] also reported similar results for sugarcane bagasse.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…However, peak disappear at 1,324, 1,514 and 1604 cm − 1 when bagasse subjected to alkali pretreatment was deligni ed more e ciently in comparison with the acid pretreatments and un-treated sugarcane bagasse. Chandel et al, [14] and Zhang et al, [32] also reported similar results for sugarcane bagasse.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, one of the objectives of the pretreatment is to increase the porosity and available surface area for the enzymatic attack [51,43,32]. The morphological investigation in the present study showed a signi cant increase in the porosity and surface area after the pretreatment, thus contribute to the enhancement of subsequent enzymatic hydrolysis [37,43,32].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For instance, at 897 cm -1 , the peak obtained was more intense in cases of acid pretreated sugarcane bagasse compared with untreated and alkali-pretreated sugarcane bagasse. In the presence of amorphous cellulose, the band at 897 cm -1 , which characterizes the C-O-C stretching at β-1,4glycosidic linkage, is strong and sharp [44][45]17]. The intensity of the regenerated cellulose band is relatively stronger than that of the original cellulose.…”
Section: Fourier Transforms Infrared (Ftir) Spectroscopymentioning
confidence: 98%